2017
DOI: 10.3233/prm-170458
|View full text |Cite
|
Sign up to set email alerts
|

Advanced skeletal maturity in children and adolescents with myelomeningocele

Abstract: Advanced skeletal maturity is common in children/adolescents with MM over 8 years of age who have reached puberty (65%), particularly those who are overweight (80%). Hormonal effects associated with adiposity and sexual maturity likely influence skeletal maturation. Clinicians may use Tanner stage and weight or BMI to gain insight into skeletal maturity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Subsequently, these etiologies must be ruled out when more concerning symptoms are present 4,6,7,12 . More rarely, advanced skeletal maturity and precocious puberty has been observed in the setting of CNS disease, such as tumors involving the hypothalamus, including pinealomas and benign hamartomas, gliomas or astrocytomas, congenital brain disorders, acquired injures, or infection 12,13 . It is important to remember that precocious puberty is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, these etiologies must be ruled out when more concerning symptoms are present 4,6,7,12 . More rarely, advanced skeletal maturity and precocious puberty has been observed in the setting of CNS disease, such as tumors involving the hypothalamus, including pinealomas and benign hamartomas, gliomas or astrocytomas, congenital brain disorders, acquired injures, or infection 12,13 . It is important to remember that precocious puberty is rare.…”
Section: Discussionmentioning
confidence: 99%
“…In more detailed analyses, we also examined the effects of neurosegmental level and pubertal development. Both age and pubertal stage were included in these analyses since youth with SB may exhibit early maturation both in terms of pubertal ( 36 ) and bone ( 37 ) development. These analyses revealed that the only bone deficits evident before puberty were reduced cancellous density in both metaphyses and weighted area in the proximal metaphysis (likely due to the reduced cancellous density).…”
Section: Discussionmentioning
confidence: 99%
“…There may be several factors associated with decreased rates of leg length discrepancy in patients that underwent prenatal repair for myelomeningocele. Leg length discrepancy in patients with myelomeningocele may be due to hip dislocation, flexion contractures, atypical skeletal development, and physeal fractures [8,[11][12][13]. Patients that undergo prenatal repair are noted to have better motor development and ability to ambulate [9], which may results in lower risks of flexion contractures and fractures due to disuse osteoporosis.…”
Section: Discussionmentioning
confidence: 99%